Revision of the genus Cornukaempferia Mood & K. Larsen (Zingiberaceae), and a new species from Thailand - PIYAPORN SAENSOUK; THAWATPHONG BOONMA; SURAPON SAENSOUK (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Saensouk P, Boonma T, Saensouk S. 2022. Revision of the genus Cornukaempferia Mood & K. Larsen (Zingiberaceae), and a new species from Thailand. Biodiversitas 23: 5718-5729. Cornukaempferia Mood & K. Larsen (Zingiberaceae) is revised. Seven species of Cornukaempferia have been recognized with their updated nomenclature including C. aurantiiflora Mood & K. Larsen, C. longipetiolata Mood & K. Larsen, C. larsenii P. Saensouk, C. chayanii Yupparach & Wongsuwan, C. kamolwaniae Picheans., Yupparach & Wongsuwan, C. argentifolia Boonma & Saensouk, and a new species, namely C. srisumoniae P. Saensouk, S. Saensouk & Boonma sp. nov. A new species is found during our exploration of the diversity of Zingiberaceae in Thailand. After comparison to all previously existing species in the genus, the morphological characteristics of a new species are the most similar to C. argentifolia, but different in certain morphological characteristics. Therefore, we claim it as a new species to science under the name C. srisumoniae P. Saensouk, Saensouk & Boonma sp. nov. This new species is described here along with its illustrations, photographs, ecology, etymology, and distribution are provided. Six species are endemic and native to Thailand, while one species, namely C. larsenii P. Saensouk is native to Thailand and Laos PDR. A revised key to 7 species and descriptions is also presented.